Construction of the “Mission poCELLble” -Cellular Structure and Function: A Strategic Intervention Material (SIM) for Grade 7 Biology - Cabildo, Lucrecia (Universitas Islam Indonesia, 2024)
This study aimed to address the persistent challenges of low student mastery in Grade 7 Biology by constructing and validating a Strategic Intervention Material (SIM) titled